GUIDELINES FOR THE DEVELOPMENT OF PROJECT IMPLEMENTATION TO TEACH LESS LEARN MORE OF SCHOOL IN DOITAO CO-EDUCATIONAL NETWORK UNDER THE DISTRICT CHIANG MAI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 5 - Sompom, Suntawat; Yuttawong, Nolthawat; Chumchery, Sirikorn (Journal of MCU Nakhondhat, 2024)
These objectives of the research are 1) To study the conditions and problems in the project implementation to teach less learn more of schools in Doitao co-educational network under the district Chiang Mai primary educational service area office 5 and 2) To find guidelines for developing the project implementation to teach less learn more of schools in Doitao co-educational network under the district Chiang Mai primary educational service area office 5, The research is divided into 2 steps The target group is 129 educational institution administrators and teachers and 9 experts. Be a scholar educational administrators and educational institution administrators specify properties and select specifics. The tools uses a structured questionnaire and interview form. Data were analyzed by find frequencies, percentages, means, standard deviations. and content analysis. The research results found that: Project implementation conditions Overall it is at a high level (μ = 4.19, σ = 0.52). Arranged from highest to lowest is: Organizing activities according to plan, planning promotion and support, supervision, monitoring and evaluation. and a discussion to reflect on results and improve them, respectively. The problem in project implementation is contact and coordination with people. There is little local wisdom and other organizations to request support. Budget to procure media. Additional equipment is not enough Dissemination of work is not thorough. and the budget for teachers to disseminate their work outside is not sufficient. Guidelines for developing project are that there should be 1) Information and knowledge. Correct, up-to-date abilities and interests of personnel. 2) Plan to support the budget. Emphasize the use of local materials and provide more equipment for organizing activities for teachers and students. 3) Take the evaluation results and process them into information for use in developing activities. and 4) Two-Way communication with all relevant parties to request support for local materials in preparing event media.